Determinants of children ever born among ever-married women in Bangladesh: evidence from the Demographic and Health Survey 2017–2018. Issue 6 (29th June 2022) - Rahman, Atikur; Hossain, Zakir; Rahman, Mohammad Lutfor; Kabir, Enamul
Abstract : Objective: To investigate the prevalence of the number of children ever born (CEB) and its associated determinants among women aged 15–49 years in Bangladesh. Study design and setting: We used clustered data extracted from the last two Bangladesh Demographic and Health Surveys (BDHS 2014 and BDHS 2017–2018). A two-stage stratified sampling was used in both surveys. Mixed logistic regression modelling approach for binary responses was adapted to accommodate clustering effects via the generalised linear mixed model framework. Participants: The study is based on 15 924 ever-married women in BDHS 2017–2018 (14 119 in BDHS 2014) of Bangladesh. Results: As per the latest BDHS 2017–2018, 42.1% of reproductive women had three or more children. Age at first marriage (p<0.001, OR 0.74, 95% CI 0.666 to 0.825), age at first birth (p<0.001, OR0.54, 95% CI 0.480 to 0.607), place of residence (p<0.001, OR 0.79, 95% CI 0.712 to 0.872), exposure of media (p<0.001, OR 0.71, 95% CI 0.647 to 0.768), religion (p<0.001, OR 1.47, 95% CI 1.277 to 1.690), husband's desire more child (p<0.001, OR 1.60, 95% CI 1.428 to 1.784), women empowerment (p<0.001, OR 1.19, 95% CI 1.075 to 1.3) and wealth index (p<0.001, OR1.61, 95% CI 0.435 to 1.796) were found to be statistically significant determinants of the number of CEB among ever-married women. The number of CEB among women was negatively associated with their own educational status (p<0.001) and husbands level of education (p<0.001). Conclusion: The CEB appears to be higher among women who were married before 18 years, Muslim, illiterate, living in rural areas, had first birth before 20 years, non-exposure of media and husband's desire for more children.